[Economic evaluation of healthcare technologies: an introduction for physicians]. - Luengo-Fernández, R; Hernández-Quesada, C; Rivero-Arias, O (2011)
Economic evaluation of healthcare interventions is becoming increasingly important and are seen by decision makers as a useful tool on how best to allocate scarce resources efficiently by maximising the health of the population. It is therefore important that health care professionals understand the fundamentals of an economic analysis so that they can understand, evaluate and critically appraise published economic evaluations. This article presents an introduction to the economic analysis of health care interventions and describes the basic concepts of an economic evaluation. The authors introduce the concept of efficiency to defend the use of economic tools to guide or help decisions in healthcare. The article presents the cost-effectiveness plane as a useful instrument when presenting the results of an economic evaluation, and summarises the main ways on how costs and outcomes are measured. To help readers understand the concepts presented in this introduction, we draw on published examples of economic analyses undertaken in the field of stroke.